ANATOMI MAKRO EKONOMI REGIONAL: STUDI KASUS PROVINSI DIY - Ma’ruf, Ahmad (Semarang State University, 2009)
The purpose of this study is to determine the level of economic growth, a description of the structureof regional economy, and analysis of economic sectors of potential, the level of investment and economicstability in DIY (Yogyakarta as Special Region). The results of this study can be used as input andevaluation of regional development planning. The data used in the form of secondary data are analyzedby descriptive statistics and quantitative analysis. Analysis tool with the Shift Share Analysis (SS),Analysis of Location Quotient (LQ) which consists of the static location quotient (SLQ) and dynamiclocation quotient (DLQ), and analysis of Incremental Capital Output Ratio (ICOR). The study concludesDIY macroeconomic dynamics is in line with the national economic pattern, economic growth, inflation,investment, exports and imports and consumption. Sectors that have the largest contribution are trade,hotels and restaurants, whereas the potential to be developed is the agricultural sector, processingindustries and services.Keywords: economic growth, potential sectors, economic stability.